Plasma ficolin levels and risk of nephritis in Danish patients with systemic lupus erythematosus. Issue 2 (February 2017) - Tanha, Nima; Pilely, Katrine; Faurschou, Mikkel; Garred, Peter; Jacobsen, Søren
Abstract Given the scavenging properties of ficolins, we hypothesized that variation in the plasma concentrations of the three ficolins may be associated with development of lupus nephritis (LN), type of LN, end-stage renal disease (ESRD), and/or mortality among patients with systemic lupus erythematosus (SLE). SLE patients attending a Danish tertiary rheumatology referral center were included. Plasma concentrations of ficolin-1, ficolin-2, and ficolin-3 were determined and dichotomized by the median into high and low. LN was defined by clinical criteria; type of LN by renal biopsy; ESRD follow-up time was defined as time from onset of LN to the development of ESRD or censoring at the end of follow-up. The study included 112 SLE patients with median disease duration of 8 years of which 53 (47%) had LN at the time of inclusion. During a median follow-up of 10 years, five patients developed ESRD. Sixteen patients died. Odds ratios (ORs) of LN were 1.2 (95% CI: 0.6–2.7), 4.1 (95% CI: 1.7–9.7), and 0.9 (95% CI: 0.4–2.0) for patients with low ficolin-1, ficolin-2, and ficolin-3 plasma levels, respectively. The distribution of histological classes differed between patients with high and low plasma levels of ficolin-1 (p = 0.009). Patients with high ficolin-1 plasma levels had an increased risk of ESRD. There was no association between the levels of the analyzed plasma ficolins and mortality. Low plasma ficolin-2 levels were associated with an increased risk of having LN. High plasma levels of ficolin-1 were associated with the histological subtype of LN and development of ESRD.